Enzyme production using organic by-products as substrate in solid state fermentation / Nithiya Arumugam - Arumugam, Nithiya (2012)
Brewery spent grain (BSG) which was used as the main organic material in this research is the by-product of brewing industries. Every 100 liter of beer generates 20kg of BSG. A Malaysian brewery (Carlsberg (M) Sdn. Bhd) alone generates 31,000 tonnes of BSG yearly. Almost all the BSG are being dumped into landfills, since there is no proper and separate guideline for industrial organic waste management in Malaysia. BSG materials are rich in nutrients and high in fermentable sugar as well as lignin, cellulose and hemicellulose. Dumping this high nutritional substrate into the landfills could contribute to adverse environmental impacts, especially greenhouse gas emission and global warming in long term. It is also can be said useful resourced are being wasted. In order to avoid environmental impacts and resources wastage, BSG can be exploited as a raw material in solid state fermentation (SSF), to produce enzymes with the help of filamentous fungi. The objective of this study is to investigate the potential utilization of BSG in producing enzymes and to identify the fungi that yield higher enzyme activity at different fermentation period and incubation temperature. Chemicals at different concentrations were used in this study to identify the effect of it in inducing the enzyme activity. Five types of filamentous fungi (Aspergillus niger, Fusarium sp., Penicillium chrysogenum, Schizophyllum commune and Trichoderma sp.) were used to determine the production of five types of enzymes including laccase, lignin peroxidase, xylanase, cellulase and amylase. Among the enzymes tested, laccase showed highest activity followed by lignin peroxidase, xylanase, cellulase and amylase in all the experiments conducted. A comparative study between BSG, spent mushroom compost (SMC) and sugarcane bagasse (SCB)was conducted to compare the ability of these substrates to produce higher enzyme activity at similar condition. Results showed BSG exhibited higher enzyme activity compared to other substrates. Enzyme activity in BSG fermented with different types of filamentous fungi was tested at different incubation period (day 1 to day 10) and at different incubation temperature (20oC, 25oC, 30oC, 35oC and 40oC). Seven day fermentation at 30oC yield higher enzyme activity for all the enzymes except for amylase activity. Amylase activity was almost twice higher at 35oC compared to ii 30oC. BSG was mixed with different percentage of SCB and SMC separately, to study the effect of mixed substrates in enzyme activity. However, the mixed substrate showed lowed enzyme activity compared to single substrate. Four chemicals namely,CoCl2, CuSO4, MnSO4 and FeSO4 with five concentrations (2 g/l, 4 g/l, 6 g/l, 8 g/l and 10 g/l) used in BSG cultivated with A. niger and S. commune to study the effect of chemicals in enzyme activity induction. Both fungi showed a positive result for the chemical induction. However, S. commune showed higher enzyme activity for cellulase, laccase, lignin peroxidase and xylanase compared to A. niger. BSG fermented with A. niger and S. commune with 10 g/l CoCl2 showed highest amylase and laccase activity respectively. CuSO4 at 4 g/l and 6 g/l showed highest xylanase and cellulase activity respectively in BSG fermented by S. commune. While 6 g/l MnSO4 showed highest lignin peroxidise activity in BSG fermented by S. commune. Therefore, the optimal chemical concentration for each enzyme varies. Fungal biomass was determined by estimating the glucosamine content to perform kinetics of SSF. Consequently the fungal growth rate and fungal half-life was also determined by using first-order kinetic equation. The growth of fungus was correlated with laccase and lignin peroxidase activity, where A. niger, S. commune and Fusarium sp. showed a strong linear correlation with these enzymes. It is evident that, BSG can be utilized as a substrate in SSF for enzyme production.